The Enhancement of Entrepreneurial Competence For Primary Education - Reny Andriyanty; Dodi Wahab; Ahmad Nurdin Hasibuan; Haswan Yunaz; Asrof Murfidiyanto; Sunarsih; Jong Yoon Park; So Jung Lee; Seung Hee Bae (International Journal Of Community Service, 2023)
The purpose of this activity was to improve the competence of elementary school teachers related to the renewal of the entrepreneurial profession through the approach of student aspirations.This community service activity was implemented in collaboration between IBI Kosgoro 1957 Republic of Indonesia, Shinhan University Republic of Korea and SDN 11 Lenteng Agung Republic of Indonesia. The method of service activities consists of counselling and discussion activities. he programme had a good effect. It turned out that 22 per cent of students changed their aspirations to become entrepreneurs.The change of aspiration indicated the effect of the programme implementation.Based on the analysis of the teacher response questionnaire on the usefulness of the programme, one hundred percent stated that this service activity increased their knowledge. The success of the programme was driven by the open attitude of primary school teachers and students and the participation of all partners who were very supportive of the programme implementation.